High-density thrombus and maximum transverse diameter on multi-spiral computed tomography angiography combine to predict abdominal aortic aneurysm rupture - Liu, Heqian; Chen, Zhipeng; Tang, Chen; Fan, Haijian; Mai, Xiaoli; Cai, Jing; Qiao, Tong (Frontiers in Cardiovascular Medicine, 2022)
Objective: We attempted to measure maximum transverse diameter (MTD) of and CT values of ILT by using multi-spiral computed tomography angiography (MSCTA) to investigate the predictive value of MTD with different CT values of thrombus on the risk of AAA rupture. Methods: Forty-five intact abdominal aortic aneurysms (IAAA) and 17 ruptured abdominal aortic aneurysms (RAAA) were included in this study. MTD and CT values in their planes were measured from MSCTA images and aneurysm lumen and thrombus volumes were calculated for the range of different CT values. Results: The median of maximum CT value of thrombus at the plane of MTD was higher in RAAA (107.0 HU) than the median in IAAA (84.5 HU) (P<0.001). Univariate logistic regression analysis showed that the maximum CT value was a risk factor for RAAA (P<0.001). It was further found that the area under the ROC curve for thrombus maximum CT value in the MTD plane to predict RAAA was 0.848 (P<0.001), with a cut-off value of 97.5 HU, a sensitivity of 82.35%, and a specificity of 84.44%. And the MTD of the abnormal lumen combined with the maximum CT value at its plane predicted RAAA with an area under the ROC curve of 0.901, a sensitivity of 76.47%, and a specificity of 97.78%. The further analysis of thrombus volume in the range of different CT value showed that median thrombus volume in RAAA in the range of 30 HU 150 HU was 124.2 cm3 which was higher than the median of 81.4 cm3 in IAAA (P=0.005). To exclude confounding factors (aneurysm volume), we calculated the standardized thrombus (ILT volume/total aneurysm volume), and the thrombus volume in the range of 30 HU 150 HU in RAAA was positively correlated with the standardized thrombus volume (ρ=0.885, P<0.001), while the thrombus volume in the range of ‐100 HU 30 HU was not correlated with it (ρ= 0.309, P=0.228). Conclusions: High-density ILT shown on MSCTA in AAAs is associated with aneurysm rupture, , and its maximum transverse diameter combined with the maximum CT value in its plane is a better predictor of RAAA.